THE USE OF MOBILE-ASSISTED LANGUAGE LEARNING (MALL) TECHNOLOGY IN ENGLISH CLASS - Sasti Kartika; Aswadi Jaya; Hermansyah Hermansyah; Etty Pratiwi; Dewi Kartikasari (Esteem Journal of English Education Study Programme, 2024)
The purpose of this research is to find out the Use of Mobile Assisted Language Learning (MALL) Technology in English classes. The problem of this research is how was the use of mobile-assisted language learning (MALL) technology in English classes. The method in this study is a qualitative method. Research techniques are carried out by means of observation, interviews, and documentation. Interviews were conducted with English teachers who teach in class VII.I. This research was conducted at SMP Negeri 2 Penukal. The results of the study stated that based on the results of the documentation obtained from the data of students who had carried out WhatsApp group activities in semester 1, and data on students who are doing WhatsApp groups in semester 2 when viewed from the results, self-management and students' motivation are very strong in conducting WhatsApp group learning, students are very active in WhatsApp groups activities, because this was done during a pandemic, until now finally the use of cellular technology is still being implemented at SMP Negeri 2 Penukal. Thus the use of mobile technology is very important to be applied in schools as a medium of distance learning. Makes it easier for teachers to give assignments to students, and control students to be more active in learning.